2018
DOI: 10.1186/s13018-018-0930-y
|View full text |Cite
|
Sign up to set email alerts
|

Coatings as the useful drug delivery system for the prevention of implant-related infections

Abstract: Implant-related infections (IRIs) which led to a large amount of medical expenditure were caused by bacteria and fungi that involve the implants in the operation or in ward. Traditional treatments of IRIs were comprised of repeated radical debridement, replacement of internal fixators, and intravenous antibiotics. It needed a long time and numbers of surgeries to cure, which meant a catastrophe to patients. So how to prevent it was more important than to cure it. As an excellent local release system, coating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 141 publications
1
76
0
1
Order By: Relevance
“…For such cases, a reliable implant coating should satisfy concomitantly three criteria: (i) stimulate a broad-spectrum antibacterial activity; (ii) elicit good stability and robustness over time; and (iii) possess a durable antimicrobial action, which can span for weeks or even months. In this context, several in vivo studies have already highlighted the merits of antibacterial HAp-based coatings and the persistence of their therapeutic effects in time [68][69][70]. Akiyama et al [69] inspected in vivo the antibacterial activity of flame-sprayed silver-containing HAp (Ag-HAp) implant coatings in the medullary cavity of rat tibiae.…”
Section: Resultsmentioning
confidence: 99%
“…For such cases, a reliable implant coating should satisfy concomitantly three criteria: (i) stimulate a broad-spectrum antibacterial activity; (ii) elicit good stability and robustness over time; and (iii) possess a durable antimicrobial action, which can span for weeks or even months. In this context, several in vivo studies have already highlighted the merits of antibacterial HAp-based coatings and the persistence of their therapeutic effects in time [68][69][70]. Akiyama et al [69] inspected in vivo the antibacterial activity of flame-sprayed silver-containing HAp (Ag-HAp) implant coatings in the medullary cavity of rat tibiae.…”
Section: Resultsmentioning
confidence: 99%
“…This method did not seem to cause more infectious complications compared to external fixation, but more importantly, patients were comfortable and complications associated with external fixation were avoided. Thorough removal of infected bone and soft tissue is the prerequisite for the use of internal fixation, and it is also the core for bone infection treatment [23,24]. The goal of debridement is to achieve a viable vascularized environment and restore local immunity.…”
Section: Discussionmentioning
confidence: 99%
“…We first reported the application of this method in the humerus, and it significantly improved patients’ satisfaction and did not improve recurrence in our series (> 0.05). Recently, Pan et al [19] concluded that the local drug and barrier effect through antibiotic-impregnated cement may reduce subsequent bacterial colonization and the formation of biofilms. Although there are many advantages of this procedure and it is being used more frequently, we suggest that it may be especially suited for patients with better soft tissue envelopes (in the humerus).…”
Section: Discussionmentioning
confidence: 99%